Five-Year Follow-Up of Repeated Intravitreal Bevacizumab for Macular Edema in a Pediatric Patient with Retinal Arteriovenous Malformation and Excellent Vision - Andrew R. Miller; Ivan J. Lee; Zachary C. Wright; Monique Leys (Case Reports in Ophthalmological Medicine)
We report a case of a 9-year-old girl presenting with unilateral retinal arteriovenous malformation (AVM) with symptomatic macular edema. Over 5 years of follow-up includes optical coherence tomography (OCT), fundus photographs, and fluorescein angiography at baseline and at follow-up. Systemic and neurologic workup was completed and negative for intracranial AVM. Vision has correlated with macular edema, ranging from 20/20 to 20/80. The patient has received nine injections of intravitreal bevacizumab and has not required an injection for the last couple of years. Follow-up is ongoing.